A Case Study of Implementing Grant-Funded Integrated Care in a Community Mental Health Center - Aby, Martha (J Behav Health Serv Res, 2020)
The U.S. government funds integrated care demonstration projects to decrease health disparities for individuals with serious mental illness. Drawing on the Exploration Preparation Implementation Sustainability (EPIS) implementation framework, this case study of a community mental health clinic describes implementation barriers and sustainability challenges with grant-funded integrated care. Findings demonstrate that integrated care practices evolve during implementation and the following factors influenced sustainability: workforce rigidity, intervention clarity, policy and funding congruence between the agency and state/federal regulations, on-going support and training in practice application, and professional institutions. Implementation strategies for primary care integration within CMHCs include creating a flexible workforce, shared definition of integrated care, policy and funding congruence, and on-going support and training.